PENGEMBANGAN MODUL BERBASIS RME UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIKA SISWA KELAS XI SMK - Dina Agustin Putri; Vera Dewi Susanti; Davi Apriandi (Program Studi PGSD Universitas Flores, 2020)
This development research aims to analyze the level of validity, effectiveness, and practicality of the RME-based learning modules as well as how the modules can improve the mathematical literacy skills of grade XI students. Modules are teaching materials that can help students in the learning process. The ability of mathematical literacy is the ability to apply mathematics to mathematical problems in everyday life. In this study, researchers used the RME approach where an approach that connects mathematics in everyday life problems. So that the availability of this module can help students improve their mathematical literacy skills. RME-based modules are said to be feasible to use if they meet three criteria, namely valid, practical, and effective. In the results of the research analysis, 1) the module was declared very valid after a revision with a large percentage of 93.00%, 2) with an average student questionnaire response results 88.67 in the limited test and 77.67 in the field test so that the module was declared practical, then 3) completeness of student learning (CSL) of 98.00 in the limited test with effective criteria and 90.00 in the field test with effective criteria. In addition, the Personalized Gain Test is used to find out how effective RME-based learning modules can improve students' mathematical literacy skills. 4) The results of the analysis of the Gain test stated 0.80 with high information. This means that RME-based learning modules are truly said to be effective in increasing students' mathematical literacy ability.